2003
DOI: 10.1021/la035227x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Wettability of Methoxy-Terminated Self-Assembled Monolayers on Gold

Abstract: This manuscript describes the structure and wettability of self-assembled monolayers (SAMs) derived from the adsorption of a series of ω-methoxyalkanethiols (CH3O(CH2) n SH, where n = 9−14) onto the surface of gold. Using ellipsometry, polarization modulation infrared reflection absorption spectroscopy (PM-IRRAS), and contact angle measurements, the interfacial properties were examined as a function of chain length. Analysis by ellipsometry revealed a progressive increase in the thickness of the films as the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 59 publications
2
31
0
Order By: Relevance
“…The parity effect in the ν s (CH 3 ) and ν a (CH 3 ) peak intensities, also observed in previous studies, ,,, is significant because it signals the presence of orientational order at the interfaces of the SAMs prepared herein. Additionally, both the symmetric and antisymmetric CH 3 stretching modes exhibit an odd–even oscillation of their peak positions (Figures b and S12d), a characteristic hereto reported only for CH 3 O­(CH 2 ) n SAu SAMs . There is a 0.7 ± 0.2 cm –1 difference in the ν s (CH 3 ) peak positions of n even and n odd and a 1.1 ± 0.2 cm –1 difference for ν a (CH 3 ).…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…The parity effect in the ν s (CH 3 ) and ν a (CH 3 ) peak intensities, also observed in previous studies, ,,, is significant because it signals the presence of orientational order at the interfaces of the SAMs prepared herein. Additionally, both the symmetric and antisymmetric CH 3 stretching modes exhibit an odd–even oscillation of their peak positions (Figures b and S12d), a characteristic hereto reported only for CH 3 O­(CH 2 ) n SAu SAMs . There is a 0.7 ± 0.2 cm –1 difference in the ν s (CH 3 ) peak positions of n even and n odd and a 1.1 ± 0.2 cm –1 difference for ν a (CH 3 ).…”
Section: Resultsmentioning
confidence: 74%
“…Additionally, both the symmetric and antisymmetric CH 3 stretching modes exhibit an odd−even oscillation of their peak positions (Figures 4b and S12d), a characteristic hereto reported only for CH 3 O(CH 2 ) n SAu SAMs. 73 There is a 0.7 ± 0.2 cm −1 difference in the ν s (CH 3 ) peak positions of n even and n odd and a 1.1 ± 0.2 cm −1 difference for ν a (CH 3 ). This odd− even effect could originate from (i) the different interactions/ chemical environments of the CH 3 groups in SAM odd and SAM even and associated intermolecular inductive effect (CH 3 ••• CH 3 in n odd and CH 3 •••CH 2 in n even ), 73,74 (ii) a difference in the conformational disorder near the chain termini, 10,29 or (iii) the different interaction potentials of molecules (e.g., water) physisorbed to SAMs of n odd versus n even 75 .…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The motivation for this study was to address experimental work that showed that the length of a chain (odd or even number of carbon atoms) of long-chain carboxylic acid monolayers determined whether oriented growth is observed [324,331,445,446]. MD simulations were used to investigate the confirmation of head groups of both odd and even number of carbon atoms of the chains.…”
Section: Modeling Of Sam Structurementioning
confidence: 99%
“…From the literature of monolayers on gold we know several important characteristics about how molecules with these functional groups assemble into monolayers. [442][443][444] Ether bonds promote disorder in monolayers as they favor gauche over trans conformations by approximately 0.1 to 0.2 kcal mol -1 . 445 Whitesides et al…”
Section: Characterization Of Monolayers Of 1-octadecene and Amentioning
confidence: 99%